Воровской общак: роман / Владимир Шитов - Шитов Владимир (Русская бойня, 1998)
Экземпляры: аб (20231107) / Инвентарный номер: 59769 / Цена: 70.00 / Сис.шифр: Р2 / Авт.знак: Ш 64 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6